Thermal conductivity measurements and correlations of pure R1243zf and binary mixtures of R32 + R1243zf and R32 + R1234yf. (November 2021) - Kim, Dongchan; Liu, Hangtao; Yang, Xiaoxian; Yang, Fufang; Morfitt, Jackson; Arami-Niya, Arash; Ryu, Mincheol; Duan, Yuanyuan; May, Eric F.
Highlights: Thermal conductivities of R32+R1234yf and R32+R1243zf mixtures were measured. Measurements were carried out in the homogenous liquid and vapor phases. Relative combined expanded uncertainties ( k = 2) in thermal conductivity are 2.0%. Parameters of the RES-CPA model for pure R1243zf and R32 + R1243zf were fitted. The RES-CPA and ECS models yield similar agreement with the experimental data. Abstract: Thermal conductivity measurements of pure R1243zf and binary mixtures of R32 + R1243zf and R32 + R1234yf were conducted in the homogeneous liquid and vapour phases with a transient hot-wire technique. The mole fractions of R32 are 0.25, 0.50, and 0.75 in both binary systems. The temperature range of the measurements was from (264.1 to 405.6) K with pressures ranging between (0.9 and 6.1) MPa. The transient hot-wire apparatus was validated with measurements of pure CO2 in both the liquid and vapour regions. The relative combined expanded uncertainty ( k = 2) in the experimental thermal conductivity was approximately 2.0 %. The relative deviations of the measured thermal conductivities from those calculated using the extended corresponding states (ECS) model as implemented in the software REFPROP 10 were between (−13 and 10) % in the vapour phase, and between (−14 and 1) % in the liquid phase. Additionally, the performance of a new approach to predicting fluid transport properties, the residual entropy scaling model incorporating the cubic-plus-association equation of state (RES-CPA model) was tested for these mixtures by first determining the scaling parameter of pure R1243zf. The RES-CPA model was then able to predict the mixture thermal conductivities generally within 10 %, which is similar to the ECS model; however no additional parameters were introduced to the RES-CPA model to describe binary interactions. Graphical abstract: Image, graphical abstract